Formulation and In Vitro Evaluation of Mucoadhesive Sustained Release Gels of Phytoestrogen Diarylheptanoids from Curcuma comosa for Vaginal Delivery - Ekapol Limpongsa; Peera Tabboon; Sarunya Tuntiyasawasdikul; Bungorn Sripanidkulchai; Thaned Pongjanyakul; Napaphak Jaipakdee (MDPI AG, 2023)
Diarylheptanoids (DAs) characterized by a 1,7-diphenylheptane structural skeleton are considered a novel class of phytoestrogens. The DAs available in Curcuma comosa Roxb. (C. comosa) extract demonstrated significant estrogenic activities both in vitro and in vivo. This study aimed to develop and comprehensively evaluate a mucoadhesive vaginal gel for the sustained release of DAs. Different mucoadhesive polymers as gelling agents were investigated. C. comosa ethanolic crude extract was used as a source of DAs. All C. comosa gels were light brown homogeneous with pH within 4.4-4.6. Their flow behaviors were pseudoplastic with a flow behavior index of 0.18-0.38. The viscosity at a low shear rate varied from 6.2 to 335.4 Pa·s. Their mechanical and extrudability properties were associated well with rheological properties. Polycarbophil (PCP):hydroxypropyl methylcellulose (HPMC) blends had a higher mucoadhesiveness to porcine vaginal mucosa than those of PCP-based or HPMC-based gels. All C. comosa gels exhibited a sustained, zero-order DA release pattern over 72 h. Korsmeyer and Peppas equation fitting indicated a non-Fickian, case II transport release mechanism. C. comosa gels had good physical and chemical stability under low-temperature storage for up to 12 months. PCP:HPMC-based mucoadhesive gels could be a proper delivery system for vaginal administration of DAs.